QUINOLINIUM BASED IONIC LIQUIDS AS ELECTROLYTE FOR DYE SENSITISED SOLAR CELLS (DSSC) - SELVARAJ, GOWRI (2017)
Steady economic growth and exponentially growing populations are liable for expanding energy demands. Modern energy generation methods use fossil fuels abundantly which lead to environmental problems. Alternative energy source such as solar is our best option for environmental preservation and conservation. This work examines the performance of a series of quinolinium-based ionic liquids (ILs) as part of the electrolyte system of dye sensitized solar cells (DSSCs). ILs have shown great potential as electrolyte for DSSCs due to properties such as good ionic conductivity, high stability and negligible vapor pressure.